2005
DOI: 10.1373/clinchem.2004.036665
|View full text |Cite
|
Sign up to set email alerts
|

Development of Miniaturized Competitive Immunoassays on a Protein Chip as a Screening Tool for Drugs

Abstract: Background: Doping in sports has become a serious problem. Gas chromatography-mass spectrometry (GC-MS) serves as an effective reference method, but it is limited by low throughput and is therefore not suitable for large-scale screening. Use of protein chips for highthroughput screening of all athletes for prohibited substances could become an important complementary tool to GC-MS. Methods: We developed a protein chip based on an aldehyde-activated glass slide containing 10 physically isolated arrays. The chip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The results of the chip were confirmed by the reference analysis (GC/MS) at the China Doping Control Center (one of the WADA-accredited laboratories) in Beijing. The correlation coefficient (r 2 ) for the quantitative results obtained with the protein chip and GC/MS was 0.991 [18].…”
Section: Protein Chip For High-throughput Screening Is a Promising Tomentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the chip were confirmed by the reference analysis (GC/MS) at the China Doping Control Center (one of the WADA-accredited laboratories) in Beijing. The correlation coefficient (r 2 ) for the quantitative results obtained with the protein chip and GC/MS was 0.991 [18].…”
Section: Protein Chip For High-throughput Screening Is a Promising Tomentioning
confidence: 99%
“…The assay was repeated in a 96-well plate and it was found that all the exogenous analytes, including amphetamine, had a low PBS/blank urine ratio (1.13-1. 18). This suggests that some nondoping substances in human urine may have interfered with the interaction of amphetamine and its antibody [18].…”
Section: Protein Chip For High-throughput Screening Is a Promising Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Du et al [31,32,36] developed a Protein Microarray for the detection of different prohibited drugs in various biological fluids. They printed up to ten different drug conjugates in triplicates onto an aldehyde modified glass slide including mouse IgG as internal control.…”
Section: Applicationsmentioning
confidence: 99%
“…In the recent few years microarray technology has had many applications in the areas of disease diagnosis and drug discovery. For example, we have developed protein microarrays for small molecule screening and severe acute respiratory syndrome (SARS) patient sample analysis [Du et al, 2005;Kong et al, 2005], and also DNA microarrays for the early detection of SARS coronavirus as well as for the potential side effect study in developing siRNAbased hepatitis B virus (HBV) inhibiting drugs Guo et al, 2005]. DNA microarrays permit high-throughput mutation detection approaches, such as allele-specific primer extension on microarrays [Pastinen et al, 2000], PCR/ligase detection reaction (LDR) universal array [Gerry et al, 1999], microsphere-based single-base chain extension (SBCE) [Chen et al, 2000], sequence-tagged molecular inversion probes (MIP) [Hardenbol et al, 2003], and combinatorial sequencing-byhybridization (cSBH) [Cowie et al, 2004].…”
Section: Introductionmentioning
confidence: 99%